Simulation of microtexture developments in the stir zone of friction stir-welded AZ31 Mg alloys. (July 2017) - Kim, M.S.; Jung, J.Y.; Song, Y.M.; Choi, S.-H.
Abstract: The evolution of the microtexture in the stir-zone (SZ) portion of AZ31 Mg alloys during friction stir welding (FSW) was investigated via microtexture analysis and polycrystal modeling. The microtexture distribution in as-welded specimens was characterized using electron backscatter diffraction (EBSD). EBSD analysis revealed that the FSW process induced the development of strong fiber textures in the SZ portion, and that the texture development was strongly dependent on the moving path of the material point with respect to the rotating pin. Three dimensional (3D) finite element analysis (FEA) was conducted to extract the thermo-mechanical history of the SZ portion of an AZ31 Mg alloy during the FSW process. In order to simulate the microtexture evolution in the SZ portion during the FSW process, the present study combined a visco-plastic self-consistent (VPSC) polycrystal model in which a dynamic recrystallization (DRX) scheme was implemented and 3D FEA. The thermo-mechanical history was gathered at a particular material point using 3D FEA and the unified microscopic hardening parameters were fitted with a Zener-Hollomon parameter and used as input data for the VPSC polycrystal model. The VPSC polycrystal model successfully predicted the development of strong and heterogeneous fiber textures in the SZ portion of a sample of AZ31 Mg alloy during the FSW process. Highlights: Microtexture evolution in the SZ portion of an AZ31 Mg alloy during FSW was investigated. EBSD analysis revealed that FSW induced the development of strong fiber textures in the SZ portion. 3D FEA was conducted to extract the thermo-mechanical history of the SZ portion during FSW. Unified microscopic hardening parameters for a VPSC model were fitted with a Zener-Hollomon parameter. A VPSC model successfully predicted the development of strong and heterogeneous fiber textures in the SZ portion.